(untitled) (Global Journal of Science Frontier Research, 2025)
Matter is any substance that has mass and energy. Matter has a minimum energy requirement.Matter tends to share energy with other matter to form a system of minimum energy formation. Matter moves because of this tendency. Relevant issues are discussed. Examples and evidence are listed to show how the Principles of Matter work.